Abnormal Return Analysis of the Minister of Finance's Policy - Kadek Ria Kusumayanti; Ni Made Suci (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the reaction of the Indonesian capital market to the Purbaya Effect phenomenon. The approach used is an event study with abnormal return measurements using a market adjusted model. The observation period includes a 90-day estimate window and an 11-day event window (t-5 to t+5) on five events: (1) the distribution of Rp200 trillion funds to Bank Himbara (2) the policy of not increasing cigarette excise rates in 2026 (3) the public statement of the elimination of tax amnesty (4) the public statement of the reduction in VAT rates to 10% (5) the announcement of the extension of the VAT DTP incentive until 2027. The results of the study showed no significant difference in average abnormal returns before and after the event for all events. However, the results of the one sample t-test found that there were several specific periods that produced significant abnormal returns: the event of the distribution of Rp200 trillion in funds was significant at t0, the public statement on the postponement of the cigarette excise tax increase was significant at t−4, the public statement on the elimination of the tax amnesty did not show significant abnormal returns in all periods; the public statement of the reduction in VAT showed a delayed and significant reaction at t+5; and the extension of the VAT DTP is significant at t−1. This finding reinforces the implications of semi-strong form market efficiency, where policy information tends to be quickly absorbed or even anticipated before the official announcement. It also suggests that the strength of a policy signal depends on its novelty, implementation certainty, and the level of market expectations.